A novel tri-band C-shaped slot loaded microstrip antenna - Garg A.; Katare K.K.; Singh S.; Singh S.P. (My University, 2025)
This paper presents the design and optimization of a probe-fed tri-band C-shaped slot loaded microstrip antenna that can operate in three frequency bands. The proposed antenna operating in the three frequency bands (3.50-3.60 GHz, 4.88-5.23 GHz and 6.46-6.70 GHz) with corresponding resonant frequencies of 3.55 GHz, 5.0 GHz and 6.57 GHz is designed and optimized using FEM based Ansoft HFSS software. By altering the dimensions of C-shaped slot, conventional dual band characteristics can be modified to a triple band characteristics which can support WLAN communication coverage IEEE 802.11j (4.90-5.091 GHz) and others. The proposed antenna features omni-directional characteristics over 3.50-3.60 GHz range and highly directional radiation pattern over 6.46-6.70 GHz range which are used for navigation and remote sensing respectively. © 2013 IEEE.